2018
DOI: 10.1177/0194599818764896
|View full text |Cite
|
Sign up to set email alerts
|

Upper Airway Stimulation for Obstructive Sleep Apnea: Results from the ADHERE Registry

Abstract: Objective Upper airway stimulation (UAS) is an alternative treatment option for patients unable to tolerate continuous positive airway pressure (CPAP) for the treatment of obstructive sleep apnea (OSA). Studies support the safety and efficacy of this therapy. The aim of this registry is to collect retrospective and prospective objective and subjective outcome measures across multiple institutions in the United States and Germany. To date, it represents the largest cohort of patients studied with this therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 32 publications
4
77
1
Order By: Relevance
“…However, approximately one‐third of patients have such difficulty with its chronic use that they seek other options or choose to remain untreated. Upper airway stimulation (UAS) with electrical activation of the hypoglossal nerve has been shown to be a safe and effective treatment option in controlled studies and post‐approval studies in clinical practices. This report details the results of an international registry designed to evaluate efficacy of UAS in patients with moderate to severe OSA and those who could not or would not use CPAP as a primary therapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, approximately one‐third of patients have such difficulty with its chronic use that they seek other options or choose to remain untreated. Upper airway stimulation (UAS) with electrical activation of the hypoglossal nerve has been shown to be a safe and effective treatment option in controlled studies and post‐approval studies in clinical practices. This report details the results of an international registry designed to evaluate efficacy of UAS in patients with moderate to severe OSA and those who could not or would not use CPAP as a primary therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] This appears to be confirmed by preliminary results of a worldwide UAS registry study with no BMI limits. 6 In a cohort of OSA patients looking for PAP treatment alternatives, 20% to 25% had a complete concentric collapse pattern (CCC). 11,12 Findings of this study gained interest because they demonstrated that previous tonsillectomy (TE) reduced prevalence of CCC, which is the major exclusion criterion for UAS, by almost half in a cohort of 210 PAP-intolerant patients.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely due to the low incidence of iatrogenic hypoglossal nerve weakness and the lack of alteration of the boney or soft tissue anatomy of the facial skeleton and pharynx. 14 The EAT-10 is a self-administered 10-item measure of symptoms of dysphagia. This instrument, scored on a 0-to 30-point scale, has previously been used to assess presence and severity of swallowing dysfunction and monitor treatment response, with superb test-retest reproducibility and criterion-based validity.…”
Section: Discussionmentioning
confidence: 99%